Effects of fertilization on crop production and nutrient-supplying capacity under rice-oilseed rape rotation system - Muhammad Yousaf; Jifu Li; Jianwei Lu; Tao Ren; Rihuan Cong; Shah Fahad; Xiaokun Li (Scientific Reports, 2017)
Abstract Incredible accomplishments have been achieved in agricultural production in China, but many demanding challenges for ensuring food security and environmental sustainability remain. Field experiments were conducted from 2011–2013 at three different sites, including Honghu, Shayang, and Jingzhou in China, to determine the effects of fertilization on enhancing crop productivity and indigenous nutrient-supplying capacity (INuS) in a rice (Oryza sativa L.)-rapeseed (Brassica napus L.) rotation. Four mineral fertilizer treatments (NPK, NP, NK and PK) were applied in a randomized complete block design with three replicates. Crop yields were increased by 19–41% (rice) and 61–76% (rapeseed) during the two years of rice-rapeseed rotation under NPK fertilization compared to PK fertilization across the study sites. Yield responses to fertilization were ranked NPK > NP > NK > PK, illustrating that N deficiency was the most limiting condition in a rice-rapeseed rotation, followed by P and K deficiencies. The highest and lowest N, P and K accumulations were observed under NPK and PK fertilization, respectively. The INuS of the soil decreased to a significant extent and affected rice-rapeseed rotation productivity at each site under NP, NK, and PK fertilization when compared to NPK. Based on the study results, a balanced nutrient application using NPK fertilization is a key management strategy for enhancing rice-rapeseed productivity and environmental safety.